Comparison of the surgical efficacy of total hip replacement versus hemiarthroplasty in the treatment of femoral neck fractures in elderly patients with sarcopenia. - Zhaoyang Yin; Zhuzhi Zhu; Chao Wang; Xiaolong Jia; Xiuqiang Zou (PLoS ONE)
Background Total hip arthroplasty (THA) and hemiarthroplasty (HA) are common surgical procedures for femoral neck fracture (FNF) in elderly patients; however, optimal treatment options remain controversial. Currently, limited research has compared the effectiveness of THA versus HA, specifically in patients with FNF and sarcopenia. Methods This retrospective study included data from 109 patients who fulfilled the inclusion criteria for the period between January 2015 and December 2017. Among these, 48 underwent THA, and 61 underwent hip arthroplasty (HA). The cross-sectional area (cm2) of muscle tissue at the pedicle level of the 12th thoracic vertebra (T12) was measured using chest computed tomography. The skeletal muscle index (SMI) was calculated by dividing the cross-sectional area of the muscle at the T12 pedicle by height squared. Sarcopenia was diagnosed when grip strength and SMI values were below the diagnostic cut-off value. Various factors were compared, including age, sex, SMI, body mass index (BMI), perioperative surgery-related indicators, postoperative 5-year survival, satisfaction, complication, and re-revision surgery rates between the 2 groups. Results There were no statistically significant differences between the THA and HA groups in terms of age (P =  0.227), sex (P =  0.870), SMI (P =  0.946), BMI (P =  0.310), postoperative time to ambulation (P =  0.803), length of hospitalization (P =  0.777), postoperative visual analog scale score (P =  0.933), and postoperative Harris score (P =  0.379). At the 5-year follow-up, there were no statistical differences in patient survival rate (P =  0.896), satisfaction (P =  0.945), incidence of complications (P =  0.796), or re-revision rate (P =  0.807). Patients who underwent THA had significantly longer operative times (P =  0.000) and larger surgical incisions (P =  0.000). They also experienced greater blood loss (P =  0.000) and blood transfusion volumes (P =  0.017), as well as increased hemoglobin (P =  0.000) and albumin (P =  0.000) loss. Furthermore, patients who underwent THA incurred higher surgical costs (P =  0.000). Conclusion THA and HA demonstrated comparable effectiveness and outcomes in patients with FNF and sarcopenia. HA was a less invasive and more cost-effective surgical option, making it the preferred choice.